Faktor-Faktor Penentu Partisipasi Petani dalam Penyuluhan Pertanian Era Otonomi Daerah Di Kabupaten Bogor - Dayat Dayat; Oeng Anwarudin (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2020)
Regional autonomy has made regency governments have broad authority in the implementation of agricultural extension. Agricultural extension activities emphasize the principle of community empowerment through community participation. The research aims to analyze descriptively farmer participation and analyze the factors that influence farmer participation in agricultural extension. The study was conducted in Bogor Regency, West Java. This type of research is a quantitative study with a survey approach. The population in this study were farmers who were members of farmer groups in Bogor Regency. The samples were determined using the Slovin formula and 93 respondents were obtained. Samples were selected using stratified random sampling. The research variables consisted of individual characteristics (X1), external factors (X2), extension activities (X3), program availability (X4) and farmer participation (Y). The data in this study consisted of primary data and secondary data. Primary data were obtained directly from respondents using a questionnaire. Secondary data is data on village monographs, village documents and conditions and a combination of farmer groups or farmer groups previously available that support research activities. Data processing techniques using descriptive statistical analysis and regression analysis. The results showed that farmers' participation in extension activities was high (77.42%). The factors that influence farmers' participation in agricultural extension activities are age, training, apprenticeship, perception, motivation, extension activities and program availability factors.